Entrepreneurship Skills Preference among Undergraduates’ Technology Education Students for National Development during COVID-19 Pandemic - S. A . Taiwo; Temitayo Omolara Onasanya; Samuel. A. Onasanya (Universitas Pendidikan Ganesha, 2023)
During covid-19 social distancing requirements makes limited in class teaching. To respond to these changes there has been a rapid uptake in remote and digital learning entrepreneurship education methods. This study analyzes the Entrepreneurship skills preference among undergraduates’ technology education students for National Development during covid-19 Pandemic. The study adopted for the study is survey research. The area covered in this research work is undergraduate technology education students offering technology education courses. The population for the study consists of 200 undergraduate students’ technology education students. All the 200 undergraduate technology students were participants. Descriptive statistics and Inferential statistics were used to answer the research questions with the aid of stastistical product and service solution (SPSS) version 20.0 at 0.05 level of significant. The result indicated that there was no significant difference in the mean rating of male and female on entrepreneurship skills preference among undergraduate technology education students for national development during covid-19 pandemic. The study concluded that various Problem influencing the preferred entrepreneurial skills by students during COVID-19 Pandemic. The study recommended that students should embrace entrepreneurial skill that cannot be restricted by any crisis.